2009
DOI: 10.1038/npp.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Alterations in Obsessive–Compulsive Disorder: An Anatomic Likelihood Estimation Meta-Analysis

Abstract: Many voxel-based morphometry (VBM) studies have found abnormalities in gray matter density (GMD) in obsessive-compulsive disorder (OCD). Here, we performed a quantitative meta-analysis of VBM studies contrasting OCD patients with healthy controls (HC). A literature search identified 10 articles that included 343 OCD patients and 318 HC. Anatomic likelihood estimation meta-analyses were performed to assess GMD changes in OCD patients relative to HC. GMD was smaller in parieto-frontal cortical regions, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
155
7
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(178 citation statements)
references
References 34 publications
13
155
7
3
Order By: Relevance
“…Previous studies have reported GM reduction in OCD in several regions and commonly in the frontal areas, 9,22 which were consistent with our result. On the other hand, we did not find altered volume in the basal ganglia or anterior cingulate, which has often been reported.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies have reported GM reduction in OCD in several regions and commonly in the frontal areas, 9,22 which were consistent with our result. On the other hand, we did not find altered volume in the basal ganglia or anterior cingulate, which has often been reported.…”
Section: Discussionsupporting
confidence: 83%
“…A meta-analysis reported that patients with OCD showed reduced GM in the parietofrontal cortical regions, including the supramarginal gyrus, dorsolateral prefrontal cortex (DLPFC), and orbitofrontal cortex, and increased GM in the putamen and anterior prefrontal cortex. 9 In contrast, VBM meta-analyses of ASD have brought controversial results. In ASD, NicklJockschat and associates reported disturbances in several regions, including the lateral occipital lobe, pericentral region, medial temporal lobe, and basal ganglia and proximate to the right parietal operculum, 10 and Via and associates found robust decreases in GM volume in the bilateral amygdala-hippocampus complex and the bilateral precuneus as well as a small increase in the middle-inferior frontal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] A recent review article 5 confirmed these results and concluded that structural alterations in patients with OCD are widespread and occur most probably at a network level, with cortical tissue reductions and a tendency toward increases in grey matter volume of subcortical limbic areas. These subcortical tissue increases were also corroborated by a recent meta/mega-analysis of the ENIGMA OCD imaging consortium.…”
Section: Introductionmentioning
confidence: 56%
“…However, the involvement of the serotonergic [4][5][6][7] , dopaminergic 8,9 and glutamatergic 10 systems has been demonstrated in this disorder. In addition, the orbitofrontal cortex, the cingulate cortex, the basal ganglia and regions within the parietal lobe have been implicated in its pathophysiology 7,[11][12][13] . Finally, life events related to fluctuations in the level of ovarian hormones (e.g., child birth, ovulation) have been reported to trigger or exacerbate OCD in women patients [14][15][16] , suggesting that ovarian hormones play a modulatory role in OCD 17 .…”
Section: Introductionmentioning
confidence: 99%